2022
DOI: 10.1186/s43019-021-00130-2
|View full text |Cite
|
Sign up to set email alerts
|

How to achieve an optimal alignment in medial opening wedge high tibial osteotomy?

Abstract: Medial opening wedge high tibial osteotomy (MOWHTO) is a widely used surgical treatment option for medial compartmental osteoarthritis with varus deformity. It is important that proper lower limb alignment is achieved. However, there has been no consensus about an optimal alignment in MOWHTO. Most studies suggest that achieving valgus alignment is necessary, and recent studies support slight valgus mechanical alignment of less than 3° of mechanical femorotibial angle. Overcorrection and undercorrection is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 75 publications
0
39
1
Order By: Relevance
“…High tibial osteotomy is an effective procedure for medial compartment osteoarthritis of the knee with varus deformity in middle-aged patients [1][2][3] . It reduces medial compartment pressure of the knee joint by realigning the mechanical axis of the lower extremity from medial to lateral compartment and redistributing the joint pressure, thereby reducing the pain and improving the function [4][5][6] .…”
mentioning
confidence: 99%
“…High tibial osteotomy is an effective procedure for medial compartment osteoarthritis of the knee with varus deformity in middle-aged patients [1][2][3] . It reduces medial compartment pressure of the knee joint by realigning the mechanical axis of the lower extremity from medial to lateral compartment and redistributing the joint pressure, thereby reducing the pain and improving the function [4][5][6] .…”
mentioning
confidence: 99%
“…Previous studies reported that a large opening gap was associated with LHF in medial opening wedge high tibial osteotomy (MOHTO). 8,10,14 Lee et al 14 reported that a large opening gap was a risk factor for LHF in MOHTO (OR, 1.615; 95% CI, 1.232-2.118; P = .001). Han et al 8 demonstrated that the osteotomy gap height was the only predictor of LHF (adjusted OR, 1.831; P = .016).…”
Section: Discussionmentioning
confidence: 99%
“…18 The postoperative mechanical axis (MA) was targeted to be at valgus angles of 2 to 3 degrees. 19,20 Arthroscopic procedures, including cartilage debridement, microfracture, partial meniscectomy, or meniscus repair, were performed in the medial compartment, when necessary, before the osteotomy procedure.…”
Section: Surgical Techniquesmentioning
confidence: 99%